(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Although we think of the school as a static institution, education is still evolving and changing, including the education of children with disabilities. With the adoption of the Law of Education in 2019, the Republic of Macedonia begins the process of full inclusion, which means that primary education is institutional, personnel, and content organized in a way that supports the inclusion of all students in regular primary education. At the proposal of the Bureau for development of the education, the Minister of education and science established NORMS and STANDARDS for space premises, equipment, and teaching aids for primary schools in the Republic of North Macedonia. Although it is stated that specialized teaching aids and resources, as well as assistive technologies, will be used for students with disabilities depending on their individual capabilities and needs, the coverage in the program document is very general. Hence the need to write this paper, to further determinate the specifications of the usage of teaching resources and aids in the inclusive classroom, specify on which way the teaching resources and aids aimed for typical students will become specialized, and which specific teaching resources, learning aids, and assistive technology are necessary for the student with motor impairments.